Multidisciplinary Inpatient Community Rehabilitation Programmes for Frail Older People: A Scoping Review - Muireann McDonnell; Mary Bell; Fiona Lawler; Anita Duffy; Michael Connolly (Nursing Open)
ABSTRACT Aim The aim of this review was to examine the evidence on multidisciplinary inpatient community rehabilitation intervention programmes for frail older people to establish what frailty rehabilitation programmes if any have been described within the literature and to identify gaps in knowledge and outcome measures used. Design A scoping review was conducted. Methods Using the Joanna Briggs Institute approach to scoping reviews, a comprehensive literature search was conducted accessing MEDLINE via PubMed, PsychINFO (via Proquest), CINAHL Complete (via EBSCO) and the Cochrane Library and a limited search of the grey literature was undertaken. Results Four articles met the inclusion criteria. A heterogenous approach to geriatric rehabilitation was evident across the literature. While the reported rehabilitation interventions were aimed at frail older people, the predominant focus of frailty rehabilitation programmes were on the physical functionality of the older person with an absence or limited measurement of any psychosocial, cognitive or spiritual outcomes or aspects of quality of life. Conclusion This scoping review exposed the paucity of scientific evidence supporting the need for inpatient multidisciplinary rehabilitative programmes for frail older people wishing to remain at home. Relevance to Clinical Practice Timely access to inpatient integrated frailty rehabilitation programmes can improve the quality of life and reduce the likelihood of hospital admissions for frail older people who wish to remain living in their own homes. With the current dearth of published evidence available, there is a necessity to undertake further research to understand the form, content and best models of delivery for frailty rehabilitative services for clinical, policy and practice purposes. Patient or Public Contribution There was no patient or public contribution.